A Challenging Path of Endoscopic Submucosal Dissection for Early Gastric Cancer in Malaysia - Hwong-Ruey Leow; Ahmad Najib Azmi; Shiaw-Hooi Ho; Khean-Lee Goh; Sanjiv Mahadeva (Korean Society of Gastrointestinal Endoscopy ,Korean Gastrointestinal Endoscopy Research Foundation, 2024)
Non-Indexed Publication